1994
DOI: 10.1063/1.356644
|View full text |Cite
|
Sign up to set email alerts
|

Raman monitoring of semiconductor growth

Abstract: A rapid reflectance-difference spectrometer for real-time semiconductor growth monitoring with subsecond time resolution Rev.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
19
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(22 citation statements)
references
References 11 publications
3
19
0
Order By: Relevance
“…13,21,22 The Stokes peak is more intensive than the anti-Stokes peak, which is typical under thermal equilibrium state. 23,24 In addition, the shoulder peaks emerging at 190 cm À1 and À190 cm À1 correspond to longitudinaloptical (LO) phonon mode. There is no significant Raman shift in the nanowire observed; however, the asymmetric broadening towards the low-frequency side is attributed to the strong phonon confinement effect in InSb nanowire structure.…”
mentioning
confidence: 99%
“…13,21,22 The Stokes peak is more intensive than the anti-Stokes peak, which is typical under thermal equilibrium state. 23,24 In addition, the shoulder peaks emerging at 190 cm À1 and À190 cm À1 correspond to longitudinaloptical (LO) phonon mode. There is no significant Raman shift in the nanowire observed; however, the asymmetric broadening towards the low-frequency side is attributed to the strong phonon confinement effect in InSb nanowire structure.…”
mentioning
confidence: 99%
“…Inelastically scattered light from the sample surface was collected through the central viewport of the UHV chamber allowing Raman spectra to be taken simultaneously to the deposition process. Details on this setup can be found elsewhere [13]. The 514.5 nm (for C 60 ) and 488 nm (for PTCDA) emission lines of an Ar + ion laser were used for excitation.…”
Section: Methodsmentioning
confidence: 99%
“…80 The ability to monitor epitaxial growth in situ has already been demonstrated by a number of workers. Wagner et al 81 showed how growth of InSb on Sb(111) could be measured at room temperature. Film growth was monitored between 0 and 40 nm, and it was possible to model the intensity variation to measure the film thickness (not a trivial matter because interference in the film imposes a cyclic intensity variation as a function of thickness).…”
Section: Semiconductors and Carbonmentioning
confidence: 99%